A beta type ti-v-fe-nb-al alloy having {332} < 113 > twinning-induced plasticity effect

CN117965953BActive Publication Date: 2026-10-09DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410058300.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2026-10-09
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

该方法通过控制Mo、Zr和Fe等元素的含量调控β相稳定性,使得室温条件下塑性变形过程中同时产生TRIP效应和TWIP效应,这虽然大大提升了合金的冷加工性能(冷轧变形率≥95%)和总延伸率(≥35%),但是合金整体的屈服强度较低,这也会使得合金的应用受限

Benefits of technology

[0019] 1. This invention is a multi-element Ti-V-Fe-Nb-Al metastable β-titanium alloy. By adding multiple alloying elements such as V, Fe, Nb, and Al, solid solution strengthening is achieved, thereby improving the strength of the alloy. The mass percentage of the alloy composition is V: 15.8%, Fe: 1%, Nb: 4%, Al: 1%, and Ti: balance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117965953B_ABST
    Figure CN117965953B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of titanium alloy materials, and discloses a beta type Ti-V-Fe-Nb-Al alloy with a {332}<113> twinning induced plasticity effect, which comprises Ti, V, Fe, Nb and Al elements, and the mass percentage of the alloy components is as follows: V: 15.6-16%, Fe: 0.8-1.2%, Nb: 3.8-4.2%, Al: 0.8-1.2%, and Ti: the balance. 100 , C' and G 111 ) to control the difficulty of shearing, recombination and collapse of atoms in a specific orientation, thereby controlling alloy metastable phase transformation and plastic deformation mode, designing a new Ti-V-Fe-Nb-Al alloy with a TWIP effect, and the alloy has good strength and plasticity matching, obvious work hardening behavior and good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of titanium alloy material technology, and specifically provides a material with {332} <113> β-type Ti-V-Fe-Nb-Al alloys with twin-induced plasticity can be used in aircraft parts. Background Technology

[0002] Titanium alloys possess lightweight, high strength, and high-temperature resistance, making them suitable for high-temperature components in aircraft engines and structural parts of the airframe, thus serving as a key material in the aerospace industry. With the development of aerospace technology, the importance of titanium alloys is gradually increasing. Because titanium alloys need to operate in various harsh service environments, they require excellent strength and toughness, as well as a certain degree of work hardening capability. The low plasticity and poor work hardening capability of commonly used titanium alloys limit their application prospects. Therefore, there is an urgent need to develop new high-strength, high-toughness titanium alloys suitable for harsh service environments.

[0003] In invention CN108570577A, the Beijing Institute of Aeronautical Materials of China Aero Engine Corporation proposed a method for preparing high-strength titanium alloy wire. This method mainly involves adding 6.3–7% Al by mass to obtain a high aluminum equivalent, and adding isomorphous β-stabilizing elements such as Mo, V, and Nb to strengthen the alloy. However, when the added aluminum exceeds 6%, a brittle Ti3Al phase precipitates, and the solid solution strengthening effect of Al results in an elongation of only about 8%, leading to poor strength-ductility matching in the alloy.

[0004] In the invention CN107723510A, China University of Mining and Technology proposed a high-strength, high-ductility β-titanium alloy with TRIP / TWIP effects and its preparation method. This method regulates the stability of the β-phase by controlling the content of elements such as Mo, Zr, and Fe, enabling the simultaneous generation of TRIP and TWIP effects during plastic deformation at room temperature. While this significantly improves the alloy's cold working properties (cold rolling deformation rate ≥95%) and total elongation (≥35%), the overall yield strength of the alloy is relatively low, which limits its applications.

[0005] To address the current shortcomings in the strength-ductility balance of titanium alloys, this invention utilizes a specific orientation modulus (E... 100 C′ and G 111 This guides alloy design and provides a solution with {332} <113> The β-type Ti-V-Fe-Nb-Al alloy exhibiting twin-induced plasticity has a good balance between strength and plasticity, and shows promising application prospects. Summary of the Invention

[0006] The purpose of this invention is to address the current imbalance between strength and ductility in titanium alloys by developing a material with {332} <113> β-type Ti-V-Fe-Nb-Al alloys exhibiting twin-induced plasticity have high strength and plasticity as well as good work hardening ability.

[0007] The technical solution of the present invention:

[0008] A kind of {332} <113> The β-type Ti-V-Fe-Nb-Al alloy with twin-induced plasticity includes Ti, V, Fe, Nb, and Al elements. The mass percentage of the alloy composition is V: 15.6–16%, Fe: 0.8–1.2%, Nb: 3.8–4.2%, Al: 0.8–1.2%, and Ti: balance.

[0009] The preferred composition of the above alloy is 78.2% Ti - 15.8% V - 1% Fe - 4% Nb - 1% Al by mass percentage.

[0010] The concept for achieving the above technical solution is: This invention utilizes a specific orientation modulus (E) 100 C′ and G 111 The parameters are used to evaluate whether metastable β-titanium alloys undergo metastable phase transformation and plastic deformation mode transformation, thereby guiding alloy design. This method is based on the fact that the relationship between the metastable phase and plastic deformation mode in metastable β-titanium alloys is essentially related to the ease with which atoms shear, recombine, or collapse; that is, the shearing and recombination processes of the α″ martensitic phase transformation are respectively related to… <100> β Young's modulus E in the direction 100 The tetragonal shear modulus C′ is related to the reorganization process of the O′ phase transition; the collapse process of the ω phase transition is related to... <111> β shear modulus G in the direction 111 Related; {332} <113> The shearing process of twins and <113> β shear modulus G in the direction 113 The recombination process is related to C′; {112} <111> The shearing process of twins and <111> β Oriented shear modulus G 111The smaller the specific orientation modulus value, the easier it is for atoms in the corresponding orientation to undergo shearing, recombination, and collapse. To design a novel titanium alloy with both strength and ductility, the specific orientation modulus of the alloy is controlled by adding β-phase stabilizing elements (V, Fe, and Nb) and α-phase stabilizing element Al. Adding Fe and Al helps reduce alloy costs, saves resources, and has a significant solid solution strengthening effect, greatly improving the overall strength of the alloy. Adding V and Nb, two isomorphous β-stabilizing elements, increases β-phase stability and does not significantly reduce ductility while increasing alloy strength. By controlling the alloy composition to make its specific orientation modulus value close to that of the typical TWIP-type alloy Ti-22V, it is hoped to obtain a novel Ti-V alloy with a good balance of strength and ductility.

[0011] The preparation method of the above-mentioned β-type Ti-V-Fe-Nb-Al alloy includes the following steps:

[0012] Step 1: Mix the metal raw materials corresponding to each element according to the mass percentage to obtain a metal mixture;

[0013] Step 2: Under the protection of inert gas, the metal mixture obtained in Step 1 is smelted multiple times, and after cooling, an alloy ingot is obtained.

[0014] Step 3: The alloy ingot obtained in Step 2 is solution treated in the β phase region and then water-cooled to room temperature to obtain β-type Ti-V-Fe-Nb-Al.

[0015] The smelting method described in step 2 is high-vacuum non-consumable melting, solidification furnace melting, plasma beam melting, electron beam melting, levitation furnace melting, or a combination thereof, with a smelting temperature ≥2200℃.

[0016] The solution treatment method described in step 3 is as follows: keep at around 900℃ for 1 hour, and then cool to room temperature with water.

[0017] The specific preparation method is as follows: The high-purity metal required for alloy smelting is cleaned with a mixed solution of hydrochloric acid and alcohol to remove oxides and adhering substances from the metal surface. The metal is then proportioned according to the corresponding mass percentages. The uniformly mixed alloy raw materials are repeatedly smelted in a DHL400 high-vacuum non-consumable arc furnace under argon protection to ensure uniform alloy composition, yielding an alloy button ingot with a mass of 100g. The smelting temperature is 2200℃, and the smelting frequency is 7-8 times. After the alloy is completely melted, it is held for 4 minutes to ensure uniform alloy composition. After smelting, the ingot is cooled with a water-cooled copper mold. The alloy ingot is then placed in a heat treatment furnace for solution treatment (900℃, 1h), and cooled by water quenching. Cylindrical compression specimens with a diameter of 3mm and a height of 5mm are cut from the alloy ingot using wire cutting. Compression performance tests are performed using a UTM4204X electronic testing machine, with a strain rate of 1.67×10⁻⁶.-3 s -1 The original and deformed microstructures of the alloy ingots were observed using OM.

[0018] The beneficial effects of this invention are:

[0019] 1. This invention is a multi-element Ti-V-Fe-Nb-Al metastable β-titanium alloy. By adding multiple alloying elements such as V, Fe, Nb, and Al, solid solution strengthening is achieved, thereby improving the strength of the alloy. The mass percentage of the alloy composition is V: 15.8%, Fe: 1%, Nb: 4%, Al: 1%, and Ti: balance.

[0020] 2. The addition of inexpensive Fe and Al reduces the smelting cost of the alloy. Fe has the best solid solution strengthening effect, which can significantly improve the strength of the alloy. Al has excellent solid solution strengthening effect and low density, which can improve the specific strength of the alloy.

[0021] 3. By adjusting the specific orientation modulus (E) 100 C′ and G 111 By controlling the magnitude of the TWIP (Transformation-Whipped In-Place) effect, the ease with which atoms in a specific orientation are sheared, rearranged, and collapsed can be controlled, thereby controlling the metastable phase transformation and plastic deformation mode of the alloy. A novel Ti-V-Fe-Nb-Al alloy with TWIP effect was designed, which has good strength and plasticity matching, obvious work hardening behavior, and good application prospects.

[0022] 4. This invention is a kind of {332} <113> A β-type titanium alloy exhibiting twin-induced plasticity, characterized by a high strength-ductility product (32 GPa%) and good work hardening behavior (>270 MPa). Attached Figure Description

[0023] Figure 1 It is Ti 78.2 -V 15.8 True stress-strain and work hardening rate curves of Fe1-Nb4-Al1 alloy under compression.

[0024] Figure 2 It is Ti 78.2 -V 15.8 Microstructure of Fe1-Nb4-Al1 alloy, (a) original microstructure after solution treatment; (b) microstructure after compression deformation of 5%. Detailed Implementation

[0025] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0026] The steps of this invention include: calculating the specific orientation modulus (E) after the addition of alloying elements using first-principles calculation methods.100 C′ and G 111 The size of the alloy was determined, the alloy composition was determined, and then the corresponding alloy button ingots were prepared using a high-vacuum non-consumable arc furnace. After appropriate heat treatment, compression samples were cut and subjected to mechanical property characterization and microstructure characterization.

[0027] First-principles calculations were used, and the cluster structure and model of the β phase were constructed using Materials Studio software. First-principles calculations based on density functional theory were performed using Vienna Ab-initio Simulation Packag software. A 3×3×3 body-centered cubic supercell composed of 54 Ti atoms was established. Subsequently, the system energy was calculated under various occupancy conditions when different types and numbers of atoms were substituted into the supercell in the binary Ti-X (V, Fe, Nb, and Al) system. This was used to determine the stability of the occupancy sites. The required parameters for VASP software were set, and the elastic constant (C) was calculated. 11 C 12 and C 44 ) and specific orientation modulus (E) 100 C′ and G 111 The calculation of the elastic constant is based on the fact that the uniaxial tensile deformation of a solid within the linear elastic range of the material is proportional to the applied external force, and its stress σ and strain ε are proportional. This can be expressed by Hooke's law σ = Eε, where E is Young's modulus. Extending Hooke's law to stress and state in three directions yields the generalized Hooke's law, which can be expressed as:

[0028]

[0029] In the formula, C ij Since C is the elastic constant, and the body-centered cubic structure has high symmetry, only C needs to be calculated. 11 C 12 and C 44 These three elastic constants can be used to calculate the required specific orientation modulus, as shown in the following formula:

[0030]

[0031]

[0032]

[0033] Therefore, the specific orientation modulus of titanium alloys of any composition can be calculated. The magnitude of the modulus indicates the ease with which atoms in a specific orientation are sheared, reorganized, and collapsed, thus allowing prediction of the solid solution structure and plastic deformation mode of the alloy.

[0034] First, the typical {332} was calculated. <113> The modulus (E) of Ti-22V binary alloys with twin-induced plasticity in a specific orientation 100 C′ and G 111 The values ​​are 22.8, 7.8, and 10.6 GPa, respectively. These values ​​can predict the plastic deformation mode of the alloy. To address the current problem of insufficient strength-ductility matching in titanium alloys, it is desired that the designed alloy possesses {332} <113> Twin-induced plasticity is used to improve the cold working properties and ductility of the alloy, meaning the specific orientation modulus of the alloy should be designed to be close to that of the Ti-22V alloy. Adding Fe and Al to the Ti-V alloy significantly strengthens the alloy through solid solution, increasing its overall strength. Adding Nb, a isomorphous β-stabilizing element, further enhances the stability of the β phase without significantly reducing its plasticity.

[0035] Three alloy compositions were designed: Ti-10V-1Fe-4Nb-1Al, Ti-15.8V-1Fe-4Nb-1Al, and Ti-18V-1Fe-4Nb-1Al. Specific design parameters are shown in Table 1. Among them, the specific orientation modulus of Ti-15.8V-1Fe-4Nb-1Al is close to that of Ti-22V, exhibiting {332} <113> Twin-induced plasticity effect; the specific orientation modulus of the other two alloy compositions is lower or higher, respectively, to conduct comparative analysis of the properties of different alloy compositions.

[0036] Table 1. Orientation moduli (E) of Ti-V-Fe-Nb-Al pentagonal alloys and Ti-22V. 100 C′ and G 111 )

[0037]

[0038] Example 1: Alloy composition Ti-15.8V-1Fe-4Nb-1Al (wt.%)

[0039] (1) Alloy preparation: Ti-15.8V-1Fe-4Nb-1Al alloy, high-purity Ti, V, Fe, Nb and Al alloy elements are proportioned according to mass percentage, and the alloy raw materials are repeatedly melted 7 to 8 times in a high vacuum non-consumable arc furnace under an argon atmosphere at a melting temperature of 2200℃ to make the alloy composition uniform and obtain 100g alloy button ingots.

[0040] (2) Solution treatment: The alloy button ingot obtained in step (1) is placed in a heat treatment furnace for solution treatment (900℃, 1h), and the cooling method is water quenching to obtain Ti-15.8V-1Fe-4Nb-1Al alloy.

[0041] (3) Mechanical property testing: Compression specimens with a diameter of 3 mm and a height of 5 mm were cut from the alloy ingot using wire cutting. Both ends were precision machined to ensure coaxiality during the experiment. A compression test was performed on the alloy using a UTM4204X electronic testing machine with a strain rate of 1.67 × 10⁻⁶. -3 s -1 The results show that the alloy exhibits good work hardening behavior (work hardening range > 270 MPa), a yield strength of 488 MPa, a compressive strength of 1043 MPa, and a uniform elongation of 32%.

[0042] (4) Microstructure observation: A 15×5mm solid solution microstructure sample was cut from the alloy ingot by electrical discharge machining. Additionally, the compression sample was compressed to 5% of its true strain using the same strain rate as in step (3), and then unloaded. A metallographic sample was prepared using standard metallographic preparation methods, and the original microstructure after solid solution treatment was observed using a metallographic microscope. Figure 2 a) and the deformation structure of the longitudinal section of the compression specimen ( Figure 2 b). Analysis shows that the alloy in the solid solution state consists of a single β-phase grain, and the plastic deformation mode of the alloy at room temperature is dominated by {332}<113>, exhibiting a twin-induced plasticity effect, which leads to the alloy having the above-mentioned excellent mechanical properties.

[0043] Comparative Example 1

[0044] The preparation process was the same as in Example 1, except that the composition, by mass percentage, was as follows: V: 10%, Fe: 1%, Nb: 4%, Al: 1%, Ti: balance. The titanium alloy prepared in this comparative example had a stress-induced α″ martensite microstructure during compressive deformation, a yield strength of 527 MPa, a compressive strength of 1235 MPa, and a uniform elongation of 24%.

[0045] Comparative Example 2

[0046] The preparation process was the same as in Example 1, except that the composition, by mass percentage, was as follows: V: 18%, Fe: 1%, Nb: 4%, Al: 1%, Ti: balance. The titanium alloy prepared in this comparative example exhibited a compression deformation microstructure consisting of dislocation slip bands and twins. Compared to Example 1, its twin area fraction was significantly reduced, the twinning-induced plasticity effect was not obvious, and a large number of dislocation slip bands were present within the grains. Its yield strength was 514 MPa, compressive strength was 990 MPa, and uniform elongation was 26%.

[0047] Comparing Comparative Examples 1 and 2 with Example 1, it can be seen that Example 1, due to the large amount of {332} generated during its deformation process, is superior. <113> The dynamic Hall-Page effect induced by mechanical twinning alleviates local stress concentration during deformation, resulting in good work hardening behavior (work hardening range > 270 MPa), leading to higher uniform elongation (32%) and strength-ductility product (32 GPa%), i.e., better strength-ductility matching. Comparative Example 1, compared to Example 1, reduced the V content, resulting in a decrease in its specific orientation modulus. The alloy exhibited a large amount of quenched ω phase before deformation, and its plastic deformation mechanism was stress-induced martensitic transformation. This led to high yield strength and low uniform elongation, indicating insufficient strength-ductility matching. Comparative Example 2, compared to Example 1, increased the V content, resulting in increased β stability and the generation of {332} during deformation. <113> Mechanical twins decrease accordingly, and a large number of dislocation slip bands appear in the deformed structure, resulting in a decrease in uniform elongation and strong plasticity product.

[0048] The above description is merely an embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications or equivalent changes made by those skilled in the art to the above-disclosed invention based on the technical essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A kind of {332} <113> β-type Ti-V-Fe-Nb-Al exhibiting twin-induced plasticity is characterized by, This β-type Ti-V-Fe-Nb-Al alloy includes Ti, V, Fe, Nb, and Al elements, with the following mass percentage composition: V: 15.6~16%, Fe: 0.8~1.2%, Nb: 3.8~4.2%, Al: 0.8~1.2%, and Ti: balance.

2. The β-type Ti-V-Fe-Nb-Al according to claim 1, characterized in that, The β-type Ti-V-Fe-Nb-Al alloy has a mass percentage of 78.2%Ti-15.8%V-1%Fe-4%Nb-1%Al.

3. The method for preparing the β-type Ti-V-Fe-Nb-Al alloy according to claim 1 or 2, characterized in that, Includes the following steps: Step 1: Mix the metal raw materials corresponding to each element according to the mass percentage to obtain a metal mixture; Step 2: Under the protection of inert gas, the metal mixture obtained in Step 1 is smelted multiple times, and after cooling, an alloy ingot is obtained. Step 3: The alloy ingot obtained in Step 2 is solution treated in the β phase region and then water-cooled to room temperature to obtain β-type Ti-V-Fe-Nb-Al.

4. The preparation method according to claim 3, characterized in that, The smelting method described in step 2 is high-vacuum non-consumable melting, solidification furnace melting, plasma beam melting, electron beam melting, levitation furnace melting, or a combination thereof, with a smelting temperature ≥2200℃.

5. The preparation method according to claim 3, characterized in that, The solution treatment method described in step 3 is as follows: keep at 900℃ for 1 hour, and then cool to room temperature with water.

Citation Information

Patent Citations

  • High-strength and high-plasticity beta titanium alloy with TRIP / TWIP effect and preparation method thereof

    CN107723510A

  • Preparation method of high-strength titanium alloy wire

    CN108570577A

  • Beta-type Ti-Mo-Nb-Fe alloy with {332} twinning induced plasticity effect

    CN112593118A

  • Beta-titanium alloy, method for producing a hot-rolled product based on said alloy and the uses thereof

    CN1902331A